2020
DOI: 10.1371/journal.ppat.1008923
|View full text |Cite
|
Sign up to set email alerts
|

“The structure of the Type III secretion system export gate with CdsO, an ATPase lever arm”

Abstract: Type III protein secretion systems (T3SS) deliver effector proteins from the Gram-negative bacterial cytoplasm into a eukaryotic host cell through a syringe-like, multi-protein nanomachine. Cytosolic components of T3SS include a portion of the export apparatus, which traverses the inner membrane and features the opening of the secretion channel, and the sorting complex for substrate recognition and for providing the energetics required for protein secretion. Two components critical for efficient effector expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…6 ). This conclusion is supported by the crystal structure of a FliJ homologue, CdsO, in complex with CdsV C , which is a FlhA C homologue 43 . It remains unknown how FliJ binds to FlhA L because CdsO does not bind to the linker region of CdsV C in the crystal structure.…”
Section: Discussionmentioning
confidence: 80%
“…6 ). This conclusion is supported by the crystal structure of a FliJ homologue, CdsO, in complex with CdsV C , which is a FlhA C homologue 43 . It remains unknown how FliJ binds to FlhA L because CdsO does not bind to the linker region of CdsV C in the crystal structure.…”
Section: Discussionmentioning
confidence: 80%
“…The crystal structure of a FliJ homolog, CdsO, in complex with CdsV C , which is a FlhA C homolog, has shown that CdsO binds to a large cleft between domains D4 of neighboring CdsV C subunits in the CdsV C ring structure but not to the linker region of CdsV C 34 (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of a FliJ homolog, CdsO, in complex with CdsV C , which is a FlhA C homolog, has led to the prediction that FliJ binds to a cleft between the D4 domains of neighboring FlhA C subunits ( Fig. 4 C ) ( 34 ). Thus, we propose that a larger Δψ may stabilize the interaction between FlhA C and the FHIPEP loop, thereby allowing FliJ to bind to FlhA C efficiently.…”
Section: Discussionmentioning
confidence: 99%